KAJIAN AWAL KEBUTUHAN JEMBATAN PENGHUBUNG ANTARA KAJIAN AWAL KEBUTUHAN JEMBATAN PENGHUBUNG ANTARA KAJIAN AWAL KEBUTUHAN JEMBATAN PENGHUBUNG ANTARA KAJIAN AWAL KEBUTUHAN JEMBATAN PENGHUBUNG ANTARA KAJIAN AWAL KEBUTUHAN JEMBATAN PENGHUBUNG ANTARA KAJIAN AWA - Joni Arliansyah (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
The rapid growths of population, economic and number of vehicles in Palembang cause the increment of mobility of people and goods in the city. Congestion at road sections and intersections, and capacity problem of Ampera Bridge now become the crucial problems that need to be solved. The purposes of this research are to evaluate the service condition of existing road network, to evaluate the existing transportation solution alternatives and to study the need of the bridges that connect the hilir and hulu sides of Palembang City. In this study, origin destination survey, traffic count and secondary data collection was conducted. The data was used to evaluate the existing transportation network and to build the transportation model of Palembang. JICA STRADA (System for Traffic Demand Analysis) Ver. 3 is used to analyze traffic demand. The Results indicate that transportation model that was developed can good represent the existing traffic condition of the road network. It can be seen from the value of determination coefficient (R2) i.e. 0.89. Evaluation of existing road transportation network indicates that, in peak hours, the main roads such as Jl. Ryacudu (Ampera Bridge), Jl. Kol. H. Burlian, Jl. Sudirman, Jl. A. Yani, Jl. Basuki Rahmat, Jl. A. Rivai and Jl. Veteran are saturated with the traffic. Some existing solution alternatives was evaluated and the results indicate that to solve the existing transportation problems, the Musi III Bridge and some fly overs are needed to be build to over come the existing transportation problems. The Musi IV is also need to be built before 2016.